Vis??o compartilhada de equipes de dire????o em pequenas organiza????es esportivas do terceiro setor - Santana, Leonardo Souza (2016)
This study described the characteristics of the formation and evolution of the shared vision of management teams of four third sector sports organizations. Shared vision is understood as the mental image shared by a group of individuals facing a desired future condition to be achieved. The theoretical framework of this study covered concepts related to shared vision and managerial conversation of management teams in the context of the management of small sports organizations in the Third Sector. The methodological approach was descriptive and based on qualitative research methods and the multicaso study (Yin, 2015; Eisenhardt, 1989b; Lima, 2010). The data were collected through in-depth interviews. This analysis included steps of intracause and intercaso analysis, according to the recommendations of Miles and Huberman (1994) and Lima (2010), in order to present the relationship between variables through schemas and representative tables to organize and provide greater clarity to the data of the search. For better analysis of the data, the Atlas-ti software was used in order to obtain a greater depth and level of detail of the study. The analyzes reveal that the formation and evolution of the common vision of the steering teams are fed by shared NEV (new elements of vision). These are generated in the subjectivity of the steering team members under the influence of FI (influence factors). The "strategic conversation", the "way of being", the "individual images", the "shared magens" and "the individual vision" are the most important FI to explain the phenomenon studied in all POETS cases.